Modulation of gut microbiota in targeted cancer therapy: insights on the EGFR/VEGF/KRAS pathways - Li Gong; Shixue Yang; Junli Huang; Yongsheng Li (Cancer Biology & Medicine)
The rise in the incidence of cancer globally has led to a heightened interest in targeted therapies as a form of anticancer treatment. Key oncogenic targets, including epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), and kirsten rat sarcoma viral oncogene homologue (KRAS), have emerged as focal points in the development of targeted agents. Research has investigated the impact of gut microbiota on the efficacy of various anticancer therapies, such as immunotherapy, chemotherapy, and radiotherapy. However, a notable gap exists in the literature regarding the relationship between gut microbiota and targeted agents. This review emphasizes how specific gut microbiota and gut microbiota metabolites, including butyrate, propionate, and ursodeoxycholic acid, interact with oncogenic pathways to modulate anti-tumor effects. Conversely, deoxycholic acid, lipopolysaccharide, and trimethylamine n-oxide may exert pro-tumor effects. Furthermore, modulation of the gut microbiota influences glucose and lipid metabolism, thereby enhancing the response to anti-KRAS agents and addressing diarrhea induced by tyrosine kinase inhibitors. By elucidating the connection between gut microbiota and the EGFR/VEGF/KRAS pathways, this review provides valuable insights for advancing targeted cancer therapy and optimizing treatment outcomes in clinical settings.